The growth performance and nonspecific immunity of juvenile grass carp (Ctenopharyngodon idella) affected by dietary Porphyra yezoensis polysaccharide supplementation. Issue 87 (April 2019) - Chen, Li; Zhang, Yipeng
Abstract: This study aims to investigate the effects of dietary Porphyra yezoensis polysaccharides (PPs) on growth performance and nonspecific immunity of juvenile grass carp ( Ctenopharyngodon idella ). Four hundreds of juvenile grass carps were randomly divided into four groups, i.e. one control group received basal diet and three treatment groups received diets supplemented with three different levels of PPs (1, 3, and 5 g kg −1 ) and tested for growth performance, survival percent, intestine digestive-enzyme activities, superoxide dismutase (SOD) activity, catalase (CAT) activity, glutathione peroxidase (GPx) activity, serum total protein, lysozyme, alkaline phosphatase, complement C3 and complement C4 and resistance to Aeromonas hydrophila of juvenile grass carp. After 60 days of feeding, the diet supplemented with an appropriate dose of PPs significantly increased growth performance, survival percent, intestine digestive-enzyme activities, SOD activity, CAT activity, GPx activity, serum lysozyme, alkaline phosphatase, complement C3, and complement C4 and resistance to Aeromonas hydrophila of juvenile grass carp compared with the control group and the optimum dose of PPs was found to be 3 g kg −1 . Results showed that dietary PPs can improve growth performance and nonspecific immunity of juvenile grass carps and can thus be used as a diet supplement for them. Highlights: PPs increased growth performance of grass carp. PPs increased survival percent of grass carp. PPs increased intestine digestive enzymes of grass carp. PPs increased SOD, CAT and GPx activities of grass carp. PPs increased non-specific immune parameters of grass carp.